2003
DOI: 10.1097/01.prs.0000054160.46502.d0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Complex Interphalangeal Joint Fractures with Dynamic External Traction: A Series of 20 Cases

Abstract: Data are reported for a series of 20 patients who were treated with the pins and rubbers traction system for fractures of the proximal interphalangeal joints of the long fingers. This technique allows fracture reduction with external dynamic traction and immediate active mobilization. Two patients in the series were lost to follow-up monitoring. For two others, the pins and rubbers traction system needed to be removed early (during the first week) because of intolerance or infection. Sixteen patients who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 17 publications
4
36
1
Order By: Relevance
“…Regardless of treatment technique, although inaccuracy of joint surface restoration (residual articular stepoff or gap, or central fragment depression) is sometimes associated with the presence of degenerative changes on radiographs, it does not seem to adversely affect range of motion, pain, or patient satisfaction, nor do results in these joints seem to deteriorate over time. 9,16,17,27,33 Early motion of the injured joint is also felt to be an important determinant of success, and it is cited as an explanation for the good results of the dynamic traction methods. 11,14 There are, however, numerous series describing the treatment of DFDs of the PIP joint that would seem to dispute the importance of early motion.…”
Section: The Evidencementioning
confidence: 96%
“…Regardless of treatment technique, although inaccuracy of joint surface restoration (residual articular stepoff or gap, or central fragment depression) is sometimes associated with the presence of degenerative changes on radiographs, it does not seem to adversely affect range of motion, pain, or patient satisfaction, nor do results in these joints seem to deteriorate over time. 9,16,17,27,33 Early motion of the injured joint is also felt to be an important determinant of success, and it is cited as an explanation for the good results of the dynamic traction methods. 11,14 There are, however, numerous series describing the treatment of DFDs of the PIP joint that would seem to dispute the importance of early motion.…”
Section: The Evidencementioning
confidence: 96%
“…Hynes and Giddins 2 used a simple dynamic external fixator to treat 8 pilon fractures of the PIP joint and one fracture of the IP joint of the thumb. Duteille et al 12 used the pins and rubber traction system device to treat complex fractures of the PIP joint of the finger. Keramidas and Miller 13 used the Suzuki frame to treat 5 intra-articular comminuted fractures of the thumb: 3 involved the metacarpophalangeal joint, and 2 the IP joint.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have focused on pilon fractures and dorsal fracture-dislocation of the PIP joint and on intra-articular fracture involving only one joint. [1][2][3]9,[11][12][13] To prevent pin track infection, we used 3 methods. First, at the end of the 4th week, the device was removed in the outpatient clinic without anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the outcome of various studies, which reported that an anatomically imperfectly restored joint surface, regardless of treatment, is sometimes associated with degenerative changes seen on radiographs but with a good clinical outcome. In addition, this does not always seem to affect range of motion adversely, nor do the results in these joints seem to deteriorate over time in all patients [8,10,26]. It has been suggested that early motion was an important determinant of successful outcome, not only in combating stiffness but also in promoting cartilage healing [15,17,19,29].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is often required in the presence of unstable fracturedislocations. Many surgical treatments have been described, including open reduction and internal fixation (ORIF) of the fracture [2,7,15,16,20,25], closed reduction and extension block pinning [21,32], use of a dynamic external fixation device [3,6,10,13,24,27,29], palmar plate arthroplasty [8,9,11] and hemi-hamate arthroplasty [1,5,23,35,37]. The combination of anatomic reduction and stable fixation of the fracture fragments, followed by early mobilization to prevent joint stiffness, is considered the ideal treatment.…”
Section: Introductionmentioning
confidence: 99%